A new model of connected renewable resource with power system and damping of low frequency oscillations by a new coordinated stabilizer based on modified multi-objective optimization algorithm. (October 2021) - Fan, Guangli; Yang, Fan; Guo, Peixi; Xue, Chengfeng; Gholami Farkoush, Saeid; Karimpoor Majd, Jaber
Abstract: This study was an attempted to present an organized structure of double-fed induction generator wind power plant with power oscillation damper (POD) in operational way and adjustable error-driven stabilizer to increase low-band oscillation reacted to their impacts in the energy system in state of charging. A novel non-linear stabilizer is suggested in the current research to compensate for the drawback of traditional stabilizers in monitoring the oscillation conditions which are internal and consequently to achieve better results in a greater range of disorders. Actually, the applied stabilizer is elastic and error-driven. Adjusting parameters of the suggested method properly plays a vital role in its efficiency. Consequently, the parameters set serve as an optimization problem which is solved by an algorithm of virus colony search (VCS) with several objectives time-domain and complex-domain. The reason behind using this algorithm is to make sure that solutions are not entrapped in local optima under the condition that the grid undergoes optimizing a great number of variables. The developed probabilistic method in frequency-domain chooses just the most favorable positions under the condition of providing the whole generators with stabilizer due to decreasing the initial expense. Lastly, a novel improved virus colony search algorithm with several objectives is implemented to provide solution for optimum adjusting of suggested stabilizer and power oscillation damper variables which serve as an optimization problem with several objectives. Confirming the efficiency of the planned method was conducted via concurrent use of eigenvalue analysis and time domain non-linear modeling in terms of various functioning states. The low frequency oscillations (LFOs) could be damped in the optimal way and as a result the stability performance of the case study system would develop meaningfully.